Experimental and Theoretical Study of the Effects of Rare Earth Elements on Growth and Chlorophyll of Alfalfa (Medicago sativa L.) Seedling - Song, Kexiao; Gao, Jinzhu; Li, Shuo; Sun, Yunfu; Sun, Haoyang; An, Baiyu; Hu, Tianming; He, Xueqing (Frontiers in Plant Science, 2021)
Low concentration rare earth elements (REEs) are usually beneficial to plant growth, while they are toxic at high concentration. The effects of La (10 μM, 20 μM), Ce (10 μM, 20 μM), and Tb (10 μM, 20 μM) treatments on seedling growth of alfalfa (Medicago sativa L.), which is one of the most important perennial leguminous forages in the world, were studied. The results showed that all three REEs promoted the germination of seeds in advance. The length of shoot under La (20 μM) treatment was significantly shortened (P < 0.05), and the root length was affected by low promoting and high inhibiting of La, Ce, and Tb. Moreover, chlorophyll content of all three REEs treatments decreased significantly, and the degree of decline was in the order La < Ce < Tb under the same concentration. In vitro experiments and quantum chemical calculations were further performed to explain why the REEs treatments reduced the chlorophyll content. In vitro experiments showed that La, Ce, and Tb treatments reduced the absorbance of chlorophyll, and the decrease followed the order La > Ce > Tb. Quantum chemical calculations predicted that the decrease of absorption intensity was caused by the reactions between La, Ce, Tb and chlorophyll, which formed lanthanides-chlorophyll, and there were five types of stable lanthanides-chlorophyll. So, REEs fertilizers may result in the enrichment of rare earth elements in leaves.